Спосіб розрахунку параметрів стільникової мережі зв’язку з розподіленням каналів - Кулаков, Ю. О.; Короненко, А. М. (НТУ "ХПІ", 2015)
Запропонована нова схема розподілення загального пулу каналів між голосовими викликами та даних в стільникових мережах зв’язку. В схемі на першому етапі відбувається балансування ка-налів, які обслуговують голосові виклики та дані для нових викликів. На другому етапі прогно-зується загальна кількість хендовер викликів та використовуючи адаптивний фільтр пере-розподіляється кількість зарезервованих каналів.

A new scheme of distribution of the common pool of channels between voice calls and data in mobile communication networks. In the first phase of the scheme is balancing channels that serve voice calls and data to new challenges. The second stage is projected to the total number of call and handover using adaptive filter redistributed number of reserved channels. With redundancy mechanisms can guarantee quality of service during a call, while all other controls flow of calls (local, based on measurements or calculations resources) take a single decision before the call setup based on information about the current state of the network. As the queue length depends on the number of reservedinextricably channels. To improve the quality necessary to calculate the number of channels with preset parameters queue length.
Method of calculation parameters cellular network connection with distribution channels
Keywords: механізми резервування; мобільна мережа; хендовер виклики; мультимедійний трафік; mobile network; handover calls; traffic; QoS